Implementation Web-Based Qr-Code Information System Design in Warehouse Inventory Management System Using Rapid Application Development (RAD) Method at PT Dharma Precision Parts - Anggara, Bastian; Anshor, Abdul Halim; Hadikristanto, Wahyu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to implement a web-based information system using QR-codes in warehouse inventory management using the Rapid Application Development (RAD) method. The implementation of QR-code technology is expected to increase efficiency and accuracy in the process of tracking and managing goods in warehouses. The RAD method was chosen because of its ability to speed up the system development process through rapid iteration and prototyping. The results of this implementation show significant improvements in warehouse operational efficiency as well as reduced human error in inventory recording and tracking. With a web-based information system, users can easily access and manage inventory data in real-time, increasing transparency and accuracy of information